Description of two new species of the Torymus advenus species group (Hymenoptera: Torymidae) from Mexico - Martínez-Romero, Aitor; Vera-Ortiz, Alexis; Equihua-Martínez, Armando; Estrada-Venegas, Edith G.; Tovar, David Cibrián; Janšta, Petr; Villar, Juli Pujade- (Zootaxa, 2024)
Two new species of Torymus (Hymenoptera: Torymidae) belonging to the advenus species group, Torymus tumoralis Martínez-Romero, Janšta & Pujade-Villar, sp. nov., and T. papularis Martínez-Romero, Janšta & Pujade-Villar, sp. nov., are described from Mexico. Torymus tumoralis (warreni subgroup) emerged from Andricus Hartig tumoral galls, and Melikaiella nr amphibolensis Pujade-Villar galls (Cynipidae: Cynipini) on oaks. Torymus papularis (advenus subgroup) is associated to an unidentified oak gall midge (Cecidomyiidae). Diagnosis, distribution, and data on biology of the new species are provided.